Implementation mapping for tobacco cessation in a federally qualified health center - Domlyn, Ariel M.; Crowder, Carolyn; Eisenson, Howard; Pollak, Kathryn I.; Davis, James M.; Calhoun, Patrick S.; Wilson, Sarah M. (Frontiers in Public Health, 2022)
Background Implementation mapping (IM) is a promising five-step method for guiding planning, execution, and maintenance of an innovation. Case examples are valuable for implementation practitioners to understand considerations for applying IM. This pilot study aimed to determine the feasibility of using IM within a federally qualified health center (FQHC) with limited funds and a one-year timeline. Methods An urban FQHC partnered with an academic team to employ IM for implementing a computerized strategy of tobacco cessation: the 5A’s (Ask, Advise, Assess, Assist, Arrange). Each step of IM was supplemented with theory-driven methods and frameworks. Data collection included surveys and interviews with clinic staff, analyzed via rapid data analysis. Results Medical assistants and clinicians were identified as primary implementers of the 5A’s intervention. Salient determinants of change included the perceived compatibility and relative priority of 5A’s. Performance objectives and change objectives were derived to address these determinants, along with a suite of implementation strategies. Despite indicators of adoptability and acceptability of the 5A’s, reductions in willingness to adopt the implementation package occurred over time and the intervention was not adopted by the FQHC within the study timeframe. This is likely due to the strain of the COVID-19 pandemic altering health clinic priorities. Conclusions Administratively, the five IM steps are feasible to conduct with FQHC staff within one year. However, this study did not obtain its intended outcomes. Lessons learned include the importance of re-assessing barriers over time and ensuring a longer timeframe to observe implementation outcomes.